(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
According to the Federation Dentaire Internationale (FDI) World Dental Federation, a common problem in teeth and mouth is dental caries. Caries is the most common disease and most experienced by people in the world. The coverage of health services (networking) for grade 1 school children in Indragiri Hilir Regency in 2022 shows that 13.7% of elementary school children must receive dental care caused by dental caries. In 2023, the highest number of children’s dental caries is the Tembilahan Hulu Health Center with 590 children. The purpose of this study is to find out factors related to maternal behavior in children who experience dental caries in elementary schools (SD) in the Tembilahan Hulu Health Center Working Area in 2024. This type of research is quantitative with a Cross Sectional research design. The location of the research was in 10 Elementary Schools (SD) in the Working Area of the Tembilahan Hulu Health Center. The research was carried out from January to July 2024. The population of this study was all mothers of children who had dental caries totaling 590 mothers. Sampling was carried out by proportional random sampling. The sample in the study was 100 people. The analysis used in this study is univariate, bivariate analysis with chi squre test and multivariate with multiple logistic regression test. The results of the test analysis found that there was a relationship between rainwater consumption (p value=0.000, OR= 6.892), cariogenic food (pvalue=0.007, OR= 5.045), maternal role (p value=0.016, OR=3.981), and maternal perception (p value=0.043, OR=3.890) towards maternal behavior in children with dental caries. The most dominant variable influencing maternal behavior was rainwater consumption (p value=0.000, OR= 6.892). It is hoped that the Tembilahan Hulu Health Center can carry out advocacy, atmosphere building, partnerships, empowerment and social support to elementary schools. Key Word : Rainwater, Dental Caries, Karogenic Foods, Maternal Behavior, and Maternal Perceptions.